2022
DOI: 10.1128/jvi.01995-21
|View full text |Cite
|
Sign up to set email alerts
|

The Human Liver-Expressed Lectin CD302 Restricts Hepatitis C Virus Infection

Abstract: The liver represents an immunoprivileged organ characterized by enhanced resistance to immune responses. However, the importance of liver cell-endogenous, noncytolytic innate immune responses in pathogen control is not well defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Q5VY30 (retinol-binding protein, RBP4) has been already proved to have close association with NAFLD risks, and the possible clinical implications of treating NAFLD by targeting RBP4 have been demonstrated . B2R582 is a protein highly similar to C-type lectin domain, and C-type lectin-like domain was demonstrated to be essential for HCV restriction . A0A5C2FWP9 is a kind of immunoglobulin G light chain, and it is reported that aberrant immunoglobulin production is a common feature of various chronic inflammatory liver diseases .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Q5VY30 (retinol-binding protein, RBP4) has been already proved to have close association with NAFLD risks, and the possible clinical implications of treating NAFLD by targeting RBP4 have been demonstrated . B2R582 is a protein highly similar to C-type lectin domain, and C-type lectin-like domain was demonstrated to be essential for HCV restriction . A0A5C2FWP9 is a kind of immunoglobulin G light chain, and it is reported that aberrant immunoglobulin production is a common feature of various chronic inflammatory liver diseases .…”
Section: Resultsmentioning
confidence: 99%
“…36 B2R582 is a protein highly similar to C-type lectin domain, and C-type lectin-like domain was demonstrated to be essential for HCV restriction. 37 A0A5C2FWP9 is a kind of immunoglobulin G light chain, and it is reported that aberrant immunoglobulin production is a common feature of various chronic inflammatory liver diseases. 38 Generally, all these five proteins that interacted with SOF had specific and high relevance with liver tissue and its corresponding diseases, contributing to the further discovery of unknown therapeutic targets.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, other restriction mechanisms cannot be excluded. Recently, new IFN-independent mechanisms of viral restriction have been described in hepatocytes: Among them, the IRF1 constitutive immunity 43 and the lectin CD302 driven restriction 44 have been associated with a resistance to infection by other RNA hepatitis viruses.…”
Section: Discussionmentioning
confidence: 99%
“…CD63, CD68, CD9, and CD5l (hepatic macrophage markers) were increased in ASH mice livers, while CD59a/b, CD79a/b, CD177, and CD302 were downregulated. Importantly, CD59 and CD302 have been shown to be expressed not only on immune cells, but also on hepatocytes [38][39][40]. CD79a/b is a marker of B cells [41,42], while CD177 is expressed in neutrophils [43].…”
Section: Ash/ah Pathogenesis Is Associated With Significant Changes I...mentioning
confidence: 99%